Keragaan Pertumbuhan dan Hasil Galur−Galur M7 Padi Lokal Pasang Surut Kalimantan Selatan di Desa Tanjung Harapan Kecamatan Alalak Kabupaten Barito Kuala - Mitra Mitra; Raihani Wahdah; Anna Maria Makalew (Agroekotek View, 2018)
Tidal marshland constitute sub optimal land that progressively important which is role in increasing effort of rice productions. However, in effort for exploit tidal marshland had a severally limitation. Therefore, new high yield rice variety is necessary that is possess high yield potential and broadly adaptation capacity. This research is a experiment that is be done on sour sulphate land with type B water overflowing by using agglomerate random design (RAK) one factor with 16 treatment, 2 replication and 32 unit experiment. The treatment consists of a 14 M7 lines and as comparator variety is local rice variety Cantik and high yield rice mutation result (Bestari). Observational result indicate growth of M7 line on high of plant, amount of tiller, flowering age, and harvest age having better performance than comparator variety. The performance yield component of M7 line on meaty grain, total grain, weight of grain per panicle, and weight of grain per hectare consistis low yield until equivalent. However, in weight of 1000 seeds M7 line strains did not differ from high yield rice mutation result (Bestari), but all the strains showed a weight of 1000 seeds heavier than local rice variety Cantik.